Orthostatic Intolerance in Older Persons: Etiology and Countermeasures - Goswami, Nandu; Blaber, Andrew P.; Hinghofer-Szalkay, Helmut; Montani, Jean-Pierre (Frontiers in Physiology, 2017)
Orthostatic challenge produced by upright posture may lead to syncope if the cardiovascular system is unable to maintain adequate brain perfusion. This review outlines orthostatic intolerance related to the aging process, long-term bedrest immobilization, drugs, and disease. Aging-associated illness or injury due to falls often leads to hospitalization. Given that older patients spend up to 83% of hospital admission lying in bed, immobilization - and its consequences such as physiological deconditioning, functional decline, and orthostatic intolerance - represents a central challenge in the care of the vulnerable older population. This review examines current scientific knowledge regarding orthostatic intolerance and how it comes about, thereby contributing to understanding of (patho-) physiological concepts of cardiovascular (in-) stability in ambulatory and bedrest confined senior citizens as well as in individuals with disease conditions (e.g. orthostatic intolerance in patients with diabetes mellitus, multiple sclerosis, Parkinson’s, spinal cord injury, SCI) or those on multiple medications (polypharmacy). Understanding these aspects, along with cardio-postural interactions, is particularly important as blood pressure destabilization leading to orthostatic intolerance affects 3-4% of the general population, and in 4 out of 10 cases the exact cause remains elusive. Reviewed also are countermeasures to orthostatic intolerance such as exercise, water drinking, mental arithmetic, cognitive training and respiration training in SCI patients. In addition, timing of countermeasure application is also discussed. We speculate that optimally applied countermeasures such as mental challenge maintain sympathetic activity, and improves venous return, stroke volume, and consequently, blood pressure during upright standing. Finally, this paper emphasizes the importance of an active life style in old age and why early re-mobilization following immobilization or bedrest is crucial in fall prevention in older persons.